Sexual Education In Malaysia: Accepted Or Rejected? - Mohd Mutalip, Siti Syairah (Tehran University of Medical Sciences, 2012)
BACKGROUND: Introduction to sexual education in schools was suggested by the Malaysian government as one of the effort taken in the aim to reduce the sexual-related social problems among Malaysian teenagers nowadays. This study was proposed in the aim to determine the rate of acceptance among adolescents on the implementation of sexual education in schools. METHODS: This study was conducted using questionnaires distributed to 152 pre-degree students in Faculty of Pharmacy, Universiti Teknologi MARA (UiTM), Kampus Puncak Alam, Selangor, Malaysia. Obtained data were statistically analyzed. RESULTS: Almost half (49.3%) of the respondents agreed that sexual education might help to overcome the social illness among school teenagers. Besides, a large number (77.6%) of respondents also agreed that this module should be incorporated with other core subjects compare to the feedback received on the implementation of this module on its own (28.9%). CONCLUSION: These results have provided some insight towards the perception of sexual education among the teenagers. Since most of the respondents agreed with this idea, so it might be a sign that the implementation of sexual education is almost accepted by the adolescents.